High-precision image-guided proton irradiation of mouse brain sub-volumes. (May 2020) - Suckert, Theresa; Müller, Johannes; Beyreuther, Elke; Azadegan, Behnam; Brüggemann, Anja; Bütof, Rebecca; Dietrich, Antje; Gotz, Malte; Haase, Robert; Schürer, Michael; Tillner, Falk; von Neubeck, Cläre; et al.
Highlights: Preclinical image-guided in vivo proton irradiation of brain sub-volumes. Automated and validated radiation damage indicator for stained brain sections. In vivo study demonstrates selective target irradiation (right hippocampus). Monte Carlo simulation of in vivo dose and LET distributions in mice. Abstract: Background and purpose: Proton radiotherapy offers the potential to reduce normal tissue toxicity. However, clinical safety margins, range uncertainties, and varying relative biological effectiveness (RBE) may result in a critical dose in tumor-surrounding normal tissue. To assess potential adverse effects in preclinical studies, image-guided proton mouse brain irradiation and analysis of DNA damage repair was established. Material and methods: We designed and characterized a setup to shape proton beams with 7 mm range in water and 3 mm in diameter and commissioned a Monte Carlo model for in vivo dose simulation. Cone-beam computed tomography and orthogonal X-ray imaging were used to delineate the right hippocampus and position the mice. The brains of three C3H/HeNRj mice were irradiated with 8 Gy and excised 30 min later. Initial DNA double-strand breaks were visualized by staining brain sections for cell nuclei and γH2AX. Imaged sections were analyzed with an automated and validated processing pipeline to provide a quantitative, spatially resolved radiation damage indicator. Results: The analyzed DNA damage pattern clearly visualized the radiation effect in the mouse brains and could be mapped to the simulated dose distribution. The proton beam passed the right hippocampus and stopped in the central brain region for all evaluated mice. Conclusion: We established image-guided proton irradiation of mouse brains. The clinically oriented workflow facilitates (back-) translational studies. Geometric accuracy, detailed Monte Carlo dose simulations, and cell-based assessment enable a biologically and spatially resolved analysis of radiation response and RBE.